Child marriage (girls) in Bangladesh and its remedies from Islamic perspective - Haque, Muhammad Faizul; Islam, Sumaiya; Banu, Mst. Rikta (Asian Institute of Research, 2026)
Child marriage under the age of 18 is considered as a criminal offence and a violation of the state’s constitutional law. Most of the time child marriage occurs in Bangladesh due to poverty and lack of awareness of its consequence. In Islam, it is strongly discouraged to arrange the marriage of girls without taking their full consent. However, this paper explores the present scenario of cultural practices of child marriage occurring in Bangladesh. The study will also focus on highlighting the major causes that led to child marriage under the age of puberty. The paper will also highlight the states’ constitutional law on child marriage and their jurisdiction over the issue. The current study adopts qualitative methods to meet its objectives through investigating existing available literature related to the issue concerned. The study finds that child marriage often occurs due to high-rate poverty, normative thoughts about the position of girls, high rate of uneducated parents and lack of strict implementation of constitutional law on those who are involved such kind of act in the family and in society. The study also finds through its discussion that due to early marriage young couples go through certain serious issues which affect their life crucially, i.e., psychological trauma, reproductive health issues, increasing domestic violence and increasing illiteracy rates in the family and in society. Finally, the present study will analyze how to prevent child marriage based on the Islamic teachings set by the Qur’an and Sunnah